THE INFLUENCE OF TRANSPARENCY, FINANCIAL LITERACY, AND DIGITAL MARKETING ON THE GOALS OF THE KAMPUNG DOLANAN ORGANIZATION WITH THE CONCEPT OF SOCIOPRENEURSHIP - Haya Aulia Assidiq; Ariq Fikria (This journal is published by the Vocational School of Universitas Sebelas Maret., 2024)
This study aims to analyze the influence of financial transparency, citizens' financial literacy, and digital marketing in realizing the organizational goals of Kampung Dolanan as a social-based business or sociopreneurship. This research focuses on the application of managerial practices in Dolanan Village and its influence on the welfare of residents. This study uses a qualitative approach, by means of interviews with the parties concerned to obtain information about the management of Dolanan Village which will later be processed and analyzed qualitatively to achieve clarity of research results. The results of the study show that transparency has not been carried out by the management team of Dolanan Village. Transparency affects organizational goals that have not been achieved because residents have not been able to fully supervise the management and achievement of organizational goals. The financial literacy of Karanggeneng residents is still low, illustrated by the fact that residents do not understand family financial management. Low financial literacy affects organizational goals because citizens do not know the truth of correct financial management. Digital marketing has not been done properly due to a lack of capable human resources. The lack of maximum digital marketing has affected the organization's goals which cannot attract tourists to come to Dolanan Village.